Evaluation of the Performance of Modeled and Simulated Hybrid Heat Pump Drying Systems for Industrial Applications - ISOLA, Abimbola Emmanuel; OLAKUNLE, Michael Sunday; OLAWALE, Adegboyega Surajudeen (ABUAD Journal of Engineering and Applied Sciences, 2024)
System configuration and design is one of the major factors that influence the performance of heat pump drying system. This study aimed to evaluate the performance and drying efficiency of two different configuration of hybrid heat pump drying system for heating process and drying of tomatoes slices at condensing temperature 15 ℃ and evaporating temperature 10 ℃ using calcium chloride-ethanol as adsorbate-adsorbent pair. The energetic coefficient of performance, and exergetic coefficient of performance and overall exergy efficiency of the system are 2.03, 15.6% and 17% respectively for simple adsorption-compression hybrid heat pump drying system while its specific moisture extraction rate is 0.234 kg/kWhr and specific energy consumption is 4.27 kg/kWhr. The energetic coefficient of performance, and exergetic coefficient of performance and overall exergy efficiency of the system are 2.18, 22.6% and 16% respectively for cascaded adsorption-compression hybrid heat pump drying system and its specific moisture extraction rate is 0.457 kg/kWhr and specific energy consumption is 3.17 kg/kWhr.